Prognostic value of combined LDL-C and remnant cholesterol stratification for 24-month major adverse cardiovascular events after primary PCI in patients with STEMI - Qianying Xie; Chaoyi Wang; Wenjing Zhao; Lei Cai; Changjie Yu; Liting Pang (Frontiers in Cardiovascular Medicine, 2026)
Objective This single-center prospective observational cohort study aimed to investigate the prognostic value of combined low-density lipoprotein cholesterol (LDL-C) and remnant cholesterol (RC) stratification in patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI). Methods A total of 812 STEMI patients were enrolled and stratified into four groups according to LDL-C and RC levels measured at 1-month post-PCI. The primary endpoint was 24-month major adverse cardiovascular events (MACE). Results The overall MACE rate increased stepwise across the four subgroups ( P < 0.001). Multivariate Cox regression showed that elevated RC was independently associated with MACE (HR = 1.559, 95% CI: 1.018−2.386, P = 0.041), whereas isolated high LDL-C was not (HR = 1.329, 95% CI: 0.992−1.781, P = 0.057). Compared with the low LDL-C + low RC group, the high LDL-C + high RC group carried the highest MACE risk (HR = 2.535, 95% CI: 1.591–4.041, P < 0.001), followed by the low LDL-C + high RC group (HR = 1.874, 95% CI: 1.153–3.045, P = 0.011). Conclusions Combined LDL-C and RC stratification may assist risk evaluation in STEMI patients after primary PCI. Elevated RC, rather than isolated high LDL-C, is associated with adverse outcomes, which may help identify patients with residual lipid-related risk.